Dusp4 Contributes to Anesthesia Neurotoxicity via Mediated Neural Differentiation in Primates - Yan, Jia; Li, Jingjie; Cheng, Yanyong; Zhang, Ying; Zhou, Zhenning; Zhang, Lei; Jiang, Hong (Frontiers in Cell and Developmental Biology, 2020)
Background Children who are exposed to anesthesia multiple times may undergo cognitive impairment during development. The underlying mechanism has been revealed as anesthesia-induced cognitive deficiency in young rodents and monkeys. However, the molecular mechanism of sevoflurane-induced neural development toxicity is unclear. Methods By combining RNA sequencing analysis of macaques’ prefrontal cortex and human neural differentiation, this study investigates the mechanism of sevoflurane-induced neurotoxicity in primates. Results The level of dual specificity protein phosphatase 4 (Dusp4) was significantly downregulated in non-human primates after sevoflurane treatment. We further uncovered the dynamical expression of Dusp4 during the human neural differentiation of human embryonic stem cells and found that knockdown of Dusp4 could significantly inhibit human neural differentiation. Conclusion This study indicated that Dusp4 is critically involved in the sevoflurane-induced inhibition of neural differentiation in non-human primate and the regulation of human neural differentiation. It also suggested that Dusp4 is a potential therapeutic target for preventing the sevoflurane-induced neurotoxicity in primates.